Analisis Persepsi Masyarakat Kawasan Adat Amma Toa Kajang Terhadap Muhammadiyah - Hasmiati Hasmiati (Universitas Muhammadiyah Makassar, 2017)
Abstract. This research uses field research (field research) with qualitative method. The subject of this research is with Indigenous Stakeholder, Village Apparatus, Community Leader, Religious Leader, Youth Leader, Academician and Kader Muhammadiyah who are domiciled in Adat area. Data collection by observation method, data writing method, technical data, data presentation and data recall. Triangulation is done to explain the validity of the data by using source and method triangulation. The results showed that the interaction of cadres and indigenous peoples is a positive and harmonious relationship, primary and secondary social contact because both parties are mutually understanding, profitable and long-standing cooperation. Conflicts that occur between the cadres and indigenous communities are still entangled lightly and only temporary. Indigenous people's perception of Amma Toa to Muhammadiyah is positive and negative, but still tend to Negative. It is caused by perceptions based on experience, efaluatif, contextual, selective and care. The perception of Amma Toa to Muahammadiyah is caused by internal and external factors. Factors factors that make individual perceptions different from each other and will be oriented to the individual in perceiving an object.Keywords: Pasang Rikajang, Gender, Social Culture